In Vitro Effects of Some Insecticides on Rumen Fluid Fermentation - H. El Obied, Greeballah; A. Ahmed, Faisal; H. H. Bashir, Nabil (Gezira Journal of Agricultural Science, 2021)
A study to investigate the effects of different levels (0,5,10 and 15ppm) of three insecticides (Endosulfan, Phosalone and Chlorpyrifos) on rumen fluid fermentation characteristics (rumen pH, rumen ammonia, rumen V FA and in vitro dry matter disappearance) was carried out in the laboratory of biology in the University of Gezira, Wad Medani, Sudan in 1998. The study indicated that all the levels of each insecticide significantly (P<0.05) inhibited the in vitro dry matter disappearance )IVDMD), the rumen fluid volatile fatty acids and the rumen fluid total protozoa, and elevated the rumen fluid ammonia compared to the control. However, the rumen fluid pH was not affected. Also, the study revealed that endosulfan significantly (P<0.05) inhibited the rumen protozoa and the IVDMD percent than both phosalpne and chlorpyrifos.